Niemieckie objaśnienia nawiasowe w prasie górnołużyckiej - Bura, Renata (Slavia Occidentalis, 2016)
The extraction of Upper Sorbian vocabulary with German glosses in parentheses allowed researchers to collect, in a short time, rich lexical material for study and to conduct statistical analyses, which, to some extent, helped to evaluate the role of the Upper Lusatian press in the development of the lexis of this language. The vocabulary extracted from the daily newspaper Serbske Nowiny (the issues of 2011) proved to be very interesting semantically. This collection of words illustrates the development of the Upper Sorbian lexis and reflects the social and economic changes which have taken place in recent years. The words explained in parentheses were poorly known or new.